Strategy for Developing the Professionalism of Soldiers of the 2nd Marine Arhanud Battalion in order to Increase the Readiness of Ampfibian Operations in order to Support the Main Tasks of the Marine Corps : Literature Review - Sindu Yanuarianto; Achmad Sochfan; Tamer Youssef (Yayasan Adra Karima Hubbi, 2026)
Background. Modern military landscapes are shifting rapidly due to the rise of unmanned aerial vehicles (UAVs) and high-precision threats. In Indonesia, Batalyon Arhanud 2 Marinir serves as a vital defensive node for amphibious assets, but it must overcome professional and operational hurdles to remain effective against these contemporary combat disruptions. Purpose. This study aims to formulate a comprehensive development strategy specifically designed to enhance the professionalism and operational readiness of soldiers within the battalion, ensuring they can meet the demands of modern air defense. Method. The research employs a qualitative approach, utilizing a Systematic Literature Review and SWOT analysis. These frameworks are used to evaluate current training protocols, doctrinal structures, and existing human resource policies within the Indonesian Marine Corps. Results. Findings indicate that while technical mastery is improving, operational effectiveness is often hindered by excessive ceremonial duties and a lack of specific Counter-UAS (C-UAS) doctrine. There is a clear need to move away from analog training toward automated, simulation-centered models that prioritize technological literacy. Conclusion. Developing professional excellence through technical expertise and adaptive tactics is essential for national sovereignty. Transitioning to integrated, tech-driven training represents the most viable path to creating a lethal and responsive point air defense system for the future.